2015
DOI: 10.1680/gein.14.00030
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art report: GCL shear strength and its measurement – ten-year update

Abstract: This paper presents an invited update to our 2004 state-of-the-art report and provides a comprehensive source of information on the shear strength and shear strength testing of geosynthetic clay liners (GCLs). Essential concepts of shear stress-displacement behavior and shear strength are presented, followed by detailed discussions on the laboratory measurement of the shear strength of GCLs and GCL interfaces. The paper also provides recommendations for the selection of design strength envelopes for stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 124 publications
0
9
0
1
Order By: Relevance
“…3. The GCL samples were hydrated following a two-stage hydration procedure [21,23,50]. In the first stage of hydration, the GCL sample was put into a water container, and the sample was immersed in water.…”
Section: Specimen Preparation and Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The GCL samples were hydrated following a two-stage hydration procedure [21,23,50]. In the first stage of hydration, the GCL sample was put into a water container, and the sample was immersed in water.…”
Section: Specimen Preparation and Test Proceduresmentioning
confidence: 99%
“…The direct shear apparatus with displacement control and stress control has some advantages and disadvantages. Fox and Stark [21] conducted a detailed review of the shear test equipment used to measure the internal and interfacial shear strength of GCL and concluded that direct shear remained the preferred test method. Many scholars conducted direct shear tests on GCL using large-scale apparatus as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many recent studies related to the performance of GCLs (e.g. Acikel et al, 2015;Ashe et al, 2015;Bannour and Touze-Foltz, 2015;Brachman et al, 2015;Di Emidio et al, 2015;Fox and Stark, 2015;Hanson et al, 2015;Liu et al, 2015;Mazzieri and Di Emidio, 2015;Puma et al, 2015;Rouf et al, 2016Rouf et al, , 2015bTake et al, 2015a,b in 2015 alone) but relatively few previous studies have examined the diffusion through GCLs. The latter include consideration of diffusion of sodium and chloride , some volatile organic compounds (Lake and Rowe, 2004;Rowe et al, 2005), metals , and some phenolic compounds (Mendes et al, 2013) through GCLs.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that to ensure stability of a landfill, knowledge of the shear behaviour of these interfaces is critical. This issue has been investigated thoroughly in recent decades (some of the most recent papers are Fox and Kim (2008), McCartney et al (2009), Palmeira (2009), Eid (2011), , Brachman and Sabir (2013), Vieira et al (2013), Liu and Martinez (2014), Sayeed et al (2014), Fox and Stark (2015)).…”
Section: Introductionmentioning
confidence: 99%